Uma visão histórica da equação do segundo grau: resultados iniciais de uma aplicação para alunos do 9° ano do ensino fundamental - MOITA, Francisdiony Reis (2023)
This work was developed with students of the 9th grade of elementary school, with the purpose of promoting meaningful learning through the application of a differentiated methodology on the historical context of the second degree equation, in mathematics classes. Thus, its objective was to present the initial results of an application on the second degree equation for students of the 9th year of Elementary School in a historical perspective. It is explained that the research had a quantitative and investigative nature with the purpose of finding out if the applied method produced the due effect on the students, and through the questionnaire to analyze the relevance of the application. Based on the students' responses, it was possible to verify their familiarity with the subject, analyze the level of learning based on the application of the historical context and evaluate the application of the methodology. Thus, this method was used to break the mechanistic and traditional context that is applied in classrooms. The results obtained showed a different panorama, at first, an aversion to the mathematical context with the quadratic equation was noticed, and, after the applied context, a more satisfactory result was obtained. Still, it was possible to verify that the vast majority of students have a troubled view of mathematics itself, this is occasionally due to the methods that were being applied throughout the stages of the students' school life. Therefore, with the application of the methodology, the students showed a greater interest in satisfying the objective of the work. This shows that the application of new methodologies in the educational context changes the student's view and facilitates learning.